Changes in stakeholder dynamics and salience during a mining disaster - J. Engelbrecht; A. Thomas (South African Journal of Business Management, 2017)
The objective of the study was to illustrate the consequences of management oversight, as an element of poor corporate governance, of timeous stakeholder identification and engagement during a South African mining crisis. A secondary objective was to apply Quantitative Narrative Analysis (QNA), a methodology thus far mainly used in sociological research, to the understanding of this governance problem.An historical event in the South African platinum mining industry, the Marikana mining disaster, served as the unit of analysis for this case study. By utilising QNA, changes in stakeholder dynamics and salience were identified, based on available narrative from South African and UK newspaper articles spanning the period 1-24 August, 2012. The historical timeline of events and consequences were plotted, the main actors identified and the relationships between the actors and the events, mapped. A stakeholder analysis took the form of graphical stakeholder models, facilitating meaningful interpretation of the effects of the events that occurred. A typology of stakeholder categorisation was used to plot how the classification of stakeholders changed during the course of 24 days.The methodology used lays foundations for future methodological applications of QNA within stakeholder theory and presents opportunities for improved understanding of the impact of stakeholders on a company and on each other during a crisis event. The study contributes, practically, to an understanding of the importance of stakeholder identification and engagement during times of crises in order to assist leaders in engaging appropriately and timeously with different stakeholders groups, thereby promoting sound corporate governance.
Keywords: 650